Association of Higher Methotrexate Dose With Lymphoproliferative Disease Onset in Rheumatoid Arthritis Patients. Issue 9 (September 2014) - Kameda, Tomohiro; Dobashi, Hiroaki; Miyatake, Nobuyuki; Inoo, Masayuki; Onishi, Ikuko; Kurata, Noriyuki; Mitsunaka, Hiroki; Kawakami, Kimihiro; Fukumoto, Tetsuya; Susaki, Kentaro; Izumikawa, Miharu; Nakashima, Shusaku; et al.
<x xml:space="preserve">Abstract</x> Objective Methotrexate (MTX) is used as an anchor drug for rheumatoid arthritis (RA). Lymphoproliferative disease (LPD) occasionally develops in patients treated with MTX, and is known as MTX‐associated LPD (MTX‐LPD). Although MTX‐LPD occurs mainly in RA patients, it has not been established if MTX administration is an independent risk factor for LPD in RA patients. We examined the clinical characteristics of MTX‐LPD in Japanese RA patients and attempted to determine the risk factors for MTX‐LPD development. Methods We performed a nested case–control study on RA patients. We enrolled 5, 753 RA patients from Kagawa, Japan. In age‐ and sex‐matched patients, we separated patients who did not develop LPD under MTX treatment (MTX non‐LPD group) from those that did (MTX‐LPD group) and conducted a comparative examination. We used multivariate analysis to determine the independent risk factors for MTX‐LPD onset. Results There were 28 patients in the MTX‐LPD group and 125 patients in the MTX non‐LPD group. Multivariate analysis of the parameters extracted by univariate analysis revealed that the mean MTX dose was a risk factor for MTX‐LPD after adjusting for age; therefore, higher MTX dose is associated with LPD onset in RA patients. Conclusion MTX is an independent risk factor for LPD onset in Japanese RA patients.